An integrative taxonomic reassessment of Kandelia candel (Rhizophoraceae), a true mangrove of Thailand - CHATCHAI NGERNSAENGSARUAY; SUWIMON UTHAIRATSAMEE; NITTAYA MIANMIT; TAMANAI PRAVINVONGVUTHI; CHONLAWIT SAMART (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Ngernsaengsaruay C, Uthairatsamee S, Mianmit N, Pravinvongvuthi T, Samart C. 2026. An integrative taxonomic reassessment of Kandelia candel (Rhizophoraceae), a true mangrove of Thailand. Biodiversitas 27 (2): d270210. https://doi.org/10.13057/biodiv/d270210. Kandelia candel (Rhizophoraceae, Rhizophoreae) is revised for Thailand based on an integrative taxonomic reassessment combining morphology, leaf anatomy, pollen morphology, and conservation assessment. This study aims to clarify the taxonomic identity, national distribution, and conservation status of the species through examinations of herbarium specimens and field collections. A detailed morphological description and illustrations are provided, together with notes on distribution, habitat, ecology, phenology, etymology, vernacular names, uses, and specimens examined. Leaf anatomical characters were investigated using light microscopy, pollen morphology was examined following standard palynological methods, and a preliminary conservation assessment was conducted in accordance with the IUCN Red List categories and criteria. In Thailand, K. candel occurs as a shrub or small tree and is rare, being confined to the south-eastern and peninsular regions. Leaves are bifacial and composed of five principal tissue layers, exhibiting anatomical adaptations typical of mangrove species, including thick cuticles, sunken stomata restricted to the abaxial surface, large hypodermal cells, and cork warts. Pollen grains are monads, isopolar, tricolporate, suboblate to subprolate or oblate-spheroidal in shape, small to medium in size, and characterized by perforate exine sculpturing. Although the species has a wide global Extent of Occurrence (EOO: 9,344,077.01 km²) and is assessed as Least Concern (LC) at the global level, its distribution in Thailand is highly restricted, with a small national EOO (52,021.25 km²) and Area of Occupancy (AOO: 40 km²). This national rarity has important implications for mangrove management and conservation planning, as locally limited populations may be more sensitive to habitat loss and coastal disturbance. This study represents the first integrative taxonomic revision of K. candel for Thailand and provides a baseline dataset for future national conservation assessments and studies on mangrove biodiversity.